Factors contributing to pre-service teachers’ reluctance to specialize in early primary education - Farah, Adnan Mohammad; Almulla, Esra Kaskaloglu; Musah, Mohammed Borhandden (Journal of Education and Learning (EduLearn), 2025)
This study identifies different factors that contribute to Bahraini pre-service teachers’ interest to specialize in early primary education. The sample of study comprised 108 year one and 49 foundation students enrolled in Bahrain Teachers College at the University of Bahrain. A stratified random sampling technique was used to insure the representation of all students from the foundation and the 1st year level. Results of the study showed that the most significant factors contribute to the pre-service teachers’ lack of interest in choosing early primary education specialization were, work environment factors such as classroom and school environment, early primary school students-related factors, personality-factors which relate to pre-service teachers’ personal qualities, and social factors such as lack of recognition, society and the influence of friends and colleagues. School administrators and decision makers can use the findings to improve the working conditions and environment in early primary education. The findings of the study provide baseline knowledge and data, empirical findings, and recommendations that can benefit administrators and Ministry of Education to improve the working conditions and environment in early primary education teaching profession.